Determinants of customer satisfaction in takaful (Islamic Insurance) services in Malaysia - Zaida Farhana Mohd Shaladdin; Mohd Zulkifli Mokhtar; Nur Haiza Muhammad Zawawi (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the pertinent components of satisfaction variables that could help the Takaful Insurance to identify and prioritise ways to gain customers. The study employed a quantitative research approach by conducting surveys through questionnaires to respondents from two universities in Malaysia. The findings from the research proved that service quality and the role of agents are significant towards the determinants of customer satisfaction in Takaful insurance services. However, the performances of the takaful operators are found to be insignificant to the service quality. In conclusion, takaful operators need to improve and strengthen their service quality and the role of their agents as well. As for the performance of these takaful operators, customers do not rely much on it, and takaful operators should not concentrate much on this factor while offering their services.